Preparation of ZnO/Bi2WO6 heterostructures with improved photocatalytic performance. (February 2020) - Liu, Jiaojiao; Luo, Zhanzhou; Han, Weining; Zhao, Yi; Li, Ping
Abstract: The construction of semiconductor heterojunction is considered an effective strategy to improve photocatalytic performance in degrading organic pollutants. Herein, the ZnO/Bi2 WO6 (ZBW) heterostructures were prepared by hydrothermal method, and the photocatalytic properties of the samples were evaluated by degrading methylene blue (MB) under ultraviolet light irradiation. The obtained ZBW heterostructures exhibit superior photocatalytic activity to pure ZnO and Bi2 WO6 . The photocatalytic efficiency of ZBW is 97.95%, and the total organic carbon removal of MB is 95.48% after 120 min irradiation. Recycling experiments show that ZBW maintains good photocatalytic activity and stability after four cycles of use. Electron paramagnetic resonance and free radical capture experiments demonstrate that the photogenerated holes are the primary active group of the photocatalytic reaction, whereas hydroxyl and superoxide radicals play smaller roles. The formation of ZBW heterojunction in the composite promotes the separation of photogenerated electrons and holes, greatly improving the photocatalytic performance of the material.